Biomarkers of end of shift exposure to disinfection byproducts in nurses - Ioannou, Solomon; Andrianou, Xanthi; Charisiadis, Pantelis; Makris, Konstantinos C. (My University, 2017)
Increased disinfectant use commonly takes place in hospitals and other health care settings. A cross-sectional study among active nurses in two Cypriot public hospitals (n = 179) was conducted to examine the prevalence of exposure to disinfection byproducts (DBPs), such as trihalomethanes (THMs) using both self-reported information and biomarker measurements. The objectives of this study were to: i) quantify the magnitude and variability of occupational exposure to disinfectants/DBPs in nurses, ii) generate job exposure matrices (JEM) and job task exposure matrices (JTEM) for disinfectants, and iii) assess the major determinants of urinary THMs in nurses. End of shift urinary total THM values showed high variability among the nurses, but did not differ between hospitals. The disinfectant group of alcohols/phenols was used by > 98% of nurses, followed by octenidine (82%), iodine and chlorine (39%, each), chlorhexidine (25%), formaldehyde (12%), hydrogen peroxide (11%), and peracetic acid/ammonia/quaternary ammonium compounds (QACs), all being < 8% each. Chlorine use during the past 24 hr was associated with significantly (p < 0.05) lower brominated THMs (BrTHMs) after adjusting for age, gender and BMI, while a positive association was shown for TCM and the sum of all THMs (TTHMs), albeit not significant. Nurses were exposed to nearly double the levels of TTHMs and BrTHMs (median and IQR, 1027 [560, 2475] ng/g and 323 [212, 497] ng/g, respectively) when compared to those of the general population (552 [309,989] ng/g and 152 [87,261] ng/g, respectively). This was the first occupational health dataset reporting measurements of biomarkers of end of shift exposures to disinfectants/DBPs.
Keywords: Nurses; Disinfectants; Disinfection; Exposure; Biomarker; Job exposure matrix; Healthcare